European Union environment policy and new forms of governance : a study of the implementation of the environmental impact assessment directive and the eco-management and audit scheme regulation in three member states /: a study of the implementation of the environmental impact assessment directive and the eco-management and audit scheme regulation in three member states. ([2018]) - Unknown
No abstract available